Medical Hypnotherapy for Pain Management. (1st June 2014) - Colón, Yvette; Avnet, Mark S.
ABSTRACT Questions from patients about pain conditions and analgesic pharmacotherapy and responses from authors are presented to help educate patients and make them more effective self-advocates. Hypnotherapy, its uses and process, and certification and training of hypnotherapy professionals are addressed.